Retrospective assessment of resource use and costs in two investigator-initiated randomized trials exemplified a comprehensive cost item list - Speich, B; Von Niederhäusern, B; Blum, CA; Keiser, J; Schur, N; Fürst, T; Kasenda, B; Christ-Crain, M; Hemkens, LG; Pauli-Magnus, C; Schwenkglenks, M; Briel, M (Elsevier, 2017)
Objectives Randomised clinical trials (RCTs) are costly and published information on resource requirements for their conduct is limited. To identify key factors for making RCTs more sustainable, empirical data on resource use and associated costs are needed. We aimed to retrospectively assess resource use and detailed costs of two academic, investigator-initiated RCTs using a comprehensive list of cost items. Study Desgn and Setting The resource use of two investigator-initiated RCTs (Prednisone-Trial [NCT00973154] and Oxantel-Trial [ISRCTN54577342]) was empirically assessed in a standardized manner through semi-structured interviews and a systematically developed cost item list. Using information about yearly salaries, resource use was translated into costs. Additionally, we collected all “other costs” including fixed priced items. Overall costs as well as cost of different study phases were calculated. Results The personnel time used in the Prednisone-Trial trial was approximately 2,897 working days and the overall costs were calculated to be USD 2.3 million, which was USD 700,000 more than planned. In the Oxantel-Trial 798 working days were spent and the overall costs were as originally planned USD 100,000. Cost drivers were similar between the two RCTs with recruitment delays explaining the additional costs in the Prednisone-Trial. Conclusion This case study provides an example of how to transparently assess resources and costs of RCTs, and presents detailed empirical data on type and magnitude of expenses. In the future, this model approach may serve others to plan, assess, or monitor resource use and costs of RCTs.